Using Drosophila melanogaster as a suitable platform for drug discovery from natural products in inflammatory bowel disease - Xiu, Minghui; Wang, Yixuan; Yang, Dan; Zhang, Xueyan; Dai, Yuting; Liu, Yongqi; Lin, Xingyao; Li, Botong; He, Jianzheng (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a chronic and life-treating inflammatory disease that can occur in multiple parts of the human intestine and has become a worldwide problem with a continually increasing incidence. Because of its mild early symptoms, most of them will not attract people’s attention and may cause more serious consequences. There is an urgent need for new therapeutics to prevent disease progression. Natural products have a variety of active ingredients, diverse biological activities, and low toxicity or side effects, which are the new options for preventing and treating the intestinal inflammatory diseases. Because of multiple genetic models, less ethical concerns, conserved signaling pathways with mammals, and low maintenance costs, the fruit fly Drosophila melanogaster has become a suitable model for studying mechanism and treatment strategy of IBD. Here, we review the advantages of fly model as screening platform in drug discovery, describe the conserved molecular pathways as therapetic targets for IBD between mammals and flies, dissect the feasibility of Drosophila model in IBD research, and summarize the natural products for IBD treatment using flies. This review comprehensively elaborates that the benefit of flies as a perfact model to evaluate the therapeutic potential of phytochemicals against IBD.